2022
DOI: 10.3390/f14010059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pre-Hardening and Autumn Fertilization on Biomass Allocation and Root Morphology of Pinus koraiensis Seedlings

Abstract: The effects of pre-hardening fertilization and autumn fertilization on seedling growth have been studied separately, but studies on their combined effects are relatively scarce. We studied the effects of pre-hardening fertilization type and autumn fertilization level on biomass allocation and root morphology of container-grown seedlings of Korean pine (Pinus koraiensis Sieb. et Zucc.), a valuable evergreen conifer distributed from Changbai Mountain to the Xiaoxing’an Mountains in northeastern China. Three pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Biomass is considered an important indicator that reflects plant productivity, whereas nitrogen fertilizer affects biomass distribution in various parts of the plant [23]. Previous studies discovered that N fertilizer resulted in a significant improvement in the biomass content of the entire Pinus koraiensis seedlings [24] and in parts of the stems and leaves of Guindilia trinervis [25]. The findings of this research align with the above findings.…”
Section: Morphological Growthsupporting
confidence: 87%
See 1 more Smart Citation
“…Biomass is considered an important indicator that reflects plant productivity, whereas nitrogen fertilizer affects biomass distribution in various parts of the plant [23]. Previous studies discovered that N fertilizer resulted in a significant improvement in the biomass content of the entire Pinus koraiensis seedlings [24] and in parts of the stems and leaves of Guindilia trinervis [25]. The findings of this research align with the above findings.…”
Section: Morphological Growthsupporting
confidence: 87%
“…Root length, root surface area, root volume, and root average diameter play a decisive role in nutrient uptake. Accordingly, studying the morphological characteristics of the root system is extremely important [24]. Previous studies have shown that phosphorus plays an important role in lateral root morphology and root branching [26], affecting not only root development but also nutrient availability [27].…”
Section: Morphological Growthmentioning
confidence: 99%